Homological invariants of 2-generator nontorsion groups of class 2 - Sarmin, Nor Haniza (2007)
Let R be the class of non-torsion groups of nilpotency class 2. Using their classification and non-abelian tensor squares, we determine certain homological invariants in R, such as the exterior square, the symmetric square and the Schur multiplier.